Elevated serum level of hepatocyte growth factor predicts development of new syndesmophytes in men with ankylosing spondylitis. (27th October 2020) - Deminger, Anna; Klingberg, Eva; Nurkkala, Merja; Geijer, Mats; Carlsten, Hans; Jacobsson, Lennart T H; Forsblad-d'Elia, Helena
Abstract: Objectives: To study baseline serum hepatocyte growth factor (s-HGF) as a predictor of spinal radiographic progression overall and by sex and to analyse factors correlated to changes in s-HGF in patients with AS. Methods: At baseline and the 5-year follow-up, s-HGF was analysed with ELISA. Spinal radiographs were graded according to modified Stoke Ankylosing Spondylitis Spinal Score. Radiographic progression was defined as ≥2 modified Stoke Ankylosing Spondylitis Spinal Score units/5 years or development of ≥1 syndesmophyte. Logistic regression analyses were used. Results: Of 204 baseline participants, 163 (80%) completed all examinations at the 5-year follow-up (54% men). Baseline s-HGF was significantly higher in men who developed ≥1 syndesmophyte compared with non-progressors, median (interquartile range) baseline s-HGF 1551 (1449–1898) vs 1436 (1200–1569) pg/ml, P = 0.003. The calculated optimal cut-off point for baseline s-HGF ≥1520 pg/ml showed a sensitivity of 70%, a specificity of 69% and univariate odds radio (95% CI) of 5.25 (1.69, 14.10) as predictor of development of ≥1 new syndesmophyte in men. Baseline s-HGF ≥1520 pg/ml remained significantly associated with development of ≥1 new syndesmophyte in men in an analysis adjusted for the baseline variables age, smoking, presence of syndesmophytes and CRP, odds radio 3.97 (1.36, 11.60). In women, no association with HGF and radiographic progression was found. Changes in s-HGF were positively correlated with changes in ESR and CRP. Conclusion: In this prospective cohort study elevated s-HGF was shown to be associated with development of new syndesmophytes in men with AS.